Depression, anxiety, sexual function and quality of life in women with hyperprolactinemia - Renan Massao Nakamura; Daniela Angerame Yela; Amanda Carvalho Santos; Beatriz Cipriano Ribas; Pedro Henrique Rosa e Silva; Bianca Netto Motta; Gabriela Pravatta Rezende; Cristina Laguna Benetti-Pinto (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: To evaluate anxiety, depression, sexual function and quality of life in women with hyperprolactinemia. Methods: Cross-sectional study with 80 women divided into two groups: 30 women with hyperprolactinemia (Study Group) followed and treated at the endocrine gynecology outpatient clinic and 50 women without hyperprolactinemia, with regular menstrual cycles (Control Group) followed at the family planning outpatient clinic of the State University of Campinas from June 2021 to October 2022. Sociodemographic characteristics, quality of life (SF-36 Questionnaire), sexual function (Female Sexual Function Index Questionnaire), depression (Beck Depression Inventory) and anxiety (Beck Anxiety Scale) were evaluated in both groups. Categorical variables were described as absolute frequency and percentage; numerical variables as mean and standard deviation. Comparison of numerical variables between two groups was performed by Mann-Whitney test, while categorical were compared by Chi-Square or Fisher's exact tests. Results: The mean age of women with hyperprolactinemia was 39.6±8.1 years and the Control Group was 31.2±9.5 years (p<0.001). There was no difference in anxiety scores (p=0.66), depression (p=0.08) and general sexual function (p=0.08) in both groups. However, women with hyperprolactinemia had lower scores in the domains of pain and arousal and worse functional capacity than Control Group (p<0.05). Conclusion: Women with hyperprolactinemia under treatment do not show any impairment in their anxiety, depression and sexual function when compared to women without hyperprolactinemia. However, analysis of quality of life showed that women with hyperprolactinemia have poor functional capacity.